Design, characterization and simulation of u-shaped solar collector for drying of agricultural products in Arequipa region - Mamani Calcina, Jorge Gilbert (2020)
This research belongs to the framework of appropriate technologies for sustainable rural development. This work characterizes process of heating air and drying capacity of an active solar dehydrator of forced convection distributive type to protect maximum of agricultural products from external agents. This system is based on use of solar energy to heat air entering drying chamber using a flat solar collector. To characterize its efficiency, a mathematical model based on an energy balance was developed where variables are climatic conditions of place temperature, humidity of environment, solar irradiation on inclined plane, wind speed in addition to design parameters of collector, flow of air and characteristics of materials used. Using an iterative method, they have been validated with experimental results from literature obtaining small relative errors (less than 6%). Once inlet and outlet temperature were obtained, a mathematical model was developed. Maximum drying efficiency was calculated using collector; based on experimental results with approximate values of (85 ± 10) % for two particular cases, proposing improvements. Finally, a parametric analysis was performed based on an established nominal case, to study how variations in design and operation conditions influence operation of collector by setting one of them. Results show that temperature of the air at outlet of collector is higher depends permanency time or if collector it is wider. It was also verified that temperature increases for low mass flows depending on convection coefficient. The outlet temperature increases proportionally with ambient temperature and solar irradiation; however, temperature decreases with wind speed as this causes more losses. Regarding efficiency of collector, results indicate a significant improvement when working with high mass flow rates, however this does not favor outlet temperature of collector or drying efficiency, since there is a limit value of mass flow from which are no longer getting better results. Solar irradiation coupled with ambient humidity and dimensions of collector, positively influence drying efficiency, while high ambient temperatures or winds peed penalize such efficiency. This study allows adjusting parameters of solar collector to ensure temperatures required in drying of agricultural products thus guaranteeing their quality.